2019
DOI: 10.1029/2019gl082256
|View full text |Cite
|
Sign up to set email alerts
|

Orographic Primary and Secondary Gravity Waves in the Middle Atmosphere From 16‐Year SABER Observations

Abstract: The seasonal and height dependencies of the orographic primary and larger‐scale secondary gravity waves (GWs) have been studied using the temperature profiles measured by Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) from 2002 to 2017. At ~40°S and during Southern Hemisphere winter, there is a strong GW peak over the Andes mountains that extend to z ~ 55 km. Using wind and topographic data, we show that orographic GWs break above the peak height of the stratospheric jet. At z ~ 55–65 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 73 publications
(116 reference statements)
2
43
0
Order By: Relevance
“…We also examined the mean potential energy density PE during this event and found that it departed significantly from exponential at z ∼ 55-80 km as a result of MW attenuation. This agrees with SABER and lidar observations (Lu et al, 2015, Liu et al, 2019Preusse et al, 2006;Trinh et al, 2018). We found that the PE increased exponentially from z ∼ 95 to 115 km because of the growth of the secondary and tertiary GWs, decreased at z ≃ 115-125 km because of the dissipation of most of the secondary GWs, and increased at z ∼ 125-160 km because of the growth of the tertiary GWs.…”
Section: Discussionsupporting
confidence: 91%
“…We also examined the mean potential energy density PE during this event and found that it departed significantly from exponential at z ∼ 55-80 km as a result of MW attenuation. This agrees with SABER and lidar observations (Lu et al, 2015, Liu et al, 2019Preusse et al, 2006;Trinh et al, 2018). We found that the PE increased exponentially from z ∼ 95 to 115 km because of the growth of the secondary and tertiary GWs, decreased at z ≃ 115-125 km because of the dissipation of most of the secondary GWs, and increased at z ∼ 125-160 km because of the growth of the tertiary GWs.…”
Section: Discussionsupporting
confidence: 91%
“…This energy increase cannot be justified by the slight decrease of balloon altitude after the Andes, because only 4% amplitude increase of pressure variations are expected. The hypothesis of detection of mountain gravity waves is strengthened by the seasonal observations of high activity in gravity waves domain above Andes from March to October (Hoffmann et al, 2013;Liu et al, 2019).…”
Section: Mountain Gravity Wavesmentioning
confidence: 99%
“…Using temperature data from the SABER (Sounding of the Atmosphere using Broadband Emission Radiometry) instrument onboard the TIMED (Thermosphere Ionosphere Mesosphere Energetics Dynamics) satellite, Trinh et al (2018) and X. Liu et al (2019) found that this hot spot is visible in the stratosphere and lower mesosphere, but not near the mesopause (e.g., at z ∼ 85-90 km in Figure 2 of Trinh et al, 2018). A possible explanation is that the hot spot is partially smoothed out around the mesopause because of horizontal propagation of (secondary) GWs.…”
Section: 1029/2020ja028034mentioning
confidence: 99%